Vulnerability of injection attacks against the application security of framework based websites open web access security project (OWASP) - Imam Riadi; Rusydi Umar; Wasito Sukarno (Jurnal Informatika, 2018)
The development of website applications is currently growing rapidly, but it is not followed by a good security system that can cause the number of security holes that can be entered by the attacker. The number of website applications that are vulnerable to injection attacks to make managers must be aware of and often update and immediately close the security gap. Website applications that have good security will become more secure but the application is still vulnerable to injection attacks. Updating and changing passwords periodically will be better than in fix. Many security hints and risks are released by Open Web Application Security Project (OWASP) TOP 10-2017 as well as a reference in wary of security risks in the application.